Epidemiology of Eyelid Trauma Among Filipino Patients in a Tertiary Hospital - Joanne Christine E. Macenas, MD; Alexander D. Tan, MD (Philippine Journal of Ophthalmology)
Objective: This study aims to identify the epidemiological characteristics and co-morbidities of eyelid injuries among Filipino patients seen at the Emergency and Out-patient Clinics of a single, tertiary, government, urbanbased hospital from June 2014 to June 2015.